Green Catalytic Pyrolysis: An Eco-Friendly Route for the Production of Fuels and Chemicals by Blending Oil Industry Wastes and Waste Furniture Wood. (6th September 2022) - Gift, M. D. Mohan; Verma, Savita; Prasad, Kalapala; Kathiresan, K.; Prasad, Rohi; Logeswaran, T.; Ghotekar, Suresh; Thao, D. V.; Lalvani, J. Isaac JoshuaRamesh
Abstract : Lignocellulosic biomass is converted into liquid products through pyrolysis, which can be used as an alternative fuel for heating applications and industrial chemicals. Pyrolysis liquid is a mixture of many oxygenated fractions which deteriorates its burning properties. Through specific bond cleavage reactions like deoxygenation, cracking, and decarbonylation, catalysts in the pyrolysis process can be used to improve the quality of pyrolysis liquid. In this study, biochar produced by carbonization of printed circuit boards was used for catalytic reforming processes to produce energy-rich liquids and chemicals from a mixture of karanja seed oil cake and waste furniture wood. The catalytic process was performed by changing the reactor temperature from 300°C to 700°C at 50°C intervals. The results showed a maximum liquid oil recovery of 53.9 wt% at 500°C. Compared to the noncatalytic reaction, pyrolysis of biomass with biochar recovered 11.59% more liquid. This study demonstrated a viable technique to recover more liquid products and industrial chemicals by employing sustainable catalysts from e-waste. The physical analysis of the liquid showed that the liquid can be used as a fuel for boilers and furnaces. The chemical characterization through gas chromatography-mass spectroscopy (GC-MS) showed the presence of various chemical elements used for medicinal and industrial applications.